Spectrum resource allocation method of maximizing transmission rate in cognitive heterogeneous wireless networks - Xiaoqing DONG; Lianglun CHENG; Gengzhong ZHENG; Tao WANG (Tongxin xuebao)
Aiming at the problem that it is difficult to allocate spectrum resources to secondary users efficiently in cognitive heterogeneous wireless networks with heterogeneous spectrum attributes,dynamic channel conditions and diverse service requirements,a spectrum resource allocation strategy with maximum transmission rate was proposed.Firstly,the strategy aimed at maximizing the total transmission rate,and constrained the limited spectrum resources and user service requirements to construct a non-linear multi-constrained spectrum resource allocation 0-1 planning model.Then a polynomial time complexity simplification method was designed.According to idle spectrum information,channel conditions,business requirements and allocation decision history information,and the benefit matrix was constructed and modified to achieve constraint simplification,and the execution efficiency was improved by improving the coefficient matrix transformation strategy of the traditional Hungarian algorithm.Finally,the performance of the method was compared and analyzed by experiments.Experimental results show that the proposed method has higher transmission rate and execution efficiency.